Medical Check-Up as an Effort to Prevent Disease Complications Early in Office Workers: A Literature Review Study - Muhamad Chalid As Shadiqy; Rizma Adila Syakurah; Misnaniarti Misnaniarti (Utan Kayu Publishing, 2025)
Medical Check Up (MCU) is an examination to determine a person's health periodically and his actual health condition at a certain period of time. From MCU activities, we can further examine health conditions and what diseases can be prevented by employees from an early age and then can find out what disease risk factors can occur as seen from the history of existing diseases. In Law No. 23 of 1992 article 23, a statement was obtained that occupational health and safety efforts must be carried out in all workplaces that have at least 10 employees. Most employees who seek treatment or check themselves into the clinic only based on the requests and complaints they experienced at that time, even though the diseases that come are non-communicable diseases (NCDs) for example hypertension, diabetes, hypercholesterolemia, and so on that must be prevented early and monitored properly.Therefore, this research was conducted for the screening process for non-communicable diseases so that they do not become a desirable complication due to the impact of underestimating NCDs suffered or will be suffered by employees and have a function for education so that employees are more aware of their health. This type of research is qualitative research.The methods used in data collection are field observation, questionnaires, in-depth interviews, analysis of the most diseases suffered by employees in the last 1 year. The data that has been collected is then analyzed using system theory, namely inputs, processes, outputs, feedback, and the environment. Based on this research, it will be possible to find out what problems occur in inputs, processes, feedback outputs or the environment that can affect MCU activities. The advice in this study is that checks on new and old employees can be carried out periodically with the support of the leadership to find out the employee's health condition before working in the new workplace and it is recommended that all employees be given the results of the examination as a benchmark for employees to maintain their health.